Intensi Penggunaan E-learning Guru Pendidikan Anak Usia Dini - Asti B. Adwitiya (Yayasan Literasi Sains Indonesia, 2022)
E-learning has become a solution to teaching and learning needs during the pandemic, including at the Early Childhood Education (ECE) level. This online-based learning is not impossible to implement in the future for remote classes. However, teachers' intentions to use e-learning which they took advantage of during the Covid-19 pandemic need to be analyzed to find out what factors play a role in making teachers' decisions to use e-learning. This study aims to evaluate these factors in ECE teachers. Data collection was carried out using a questionnaire given online to ECE teachers from several cities in East Java. There were 135 ECE teachers who participated in this study. The data obtained were then analyzed using multiple linear regression methods. The results of this study indicate that the intention to use e-learning is not influenced by demographic factors such as gender, age, domicile, and education. Intention to use e-learning is influenced by the main factors, namely perceived convenience, perceived usefulness, and subjective norms. These three factors can be used as considerations in preparing curriculum, methods and online learning media in the future.